2019
DOI: 10.1371/journal.pone.0222787
|View full text |Cite|
|
Sign up to set email alerts
|

Axial variation of deoxyhemoglobin density as a source of the low-frequency time lag structure in blood oxygenation level-dependent signals

Abstract: Perfusion-related information is reportedly embedded in the low-frequency component of a blood oxygen level-dependent (BOLD) functional magnetic resonance imaging (fMRI) signal. The blood-propagation pattern through the cerebral vascular tree is detected as an interregional lag variation of spontaneous low-frequency oscillations (sLFOs). Mapping of this lag, or phase, has been implicitly treated as a projection of the vascular tree structure onto real space. While accumulating evidence supports the biological … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 99 publications
(120 reference statements)
0
11
0
Order By: Relevance
“…Finally, a recently proposed denoising method 27,28 was used to cope with contamination from non-neural signal components. This procedure involves tracking regional variations of low-frequency oscillations of systemic origin, using the bandpass-filtered (0.008–0.07 Hz) global signal as an initial seed.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, a recently proposed denoising method 27,28 was used to cope with contamination from non-neural signal components. This procedure involves tracking regional variations of low-frequency oscillations of systemic origin, using the bandpass-filtered (0.008–0.07 Hz) global signal as an initial seed.…”
Section: Methodsmentioning
confidence: 99%
“…Many regions, notably arteries in the inferior slices, fluctuated at the pseudo-periodic rate of the manual ventilation and exhibited high signal variance, strongly suggesting a BOLD signal change due either to non-stationary arterial CO 2 (Tong & Frederick 2010, Tong et al . 2019) and/or non-stationary deoxyhemoglobin concentration in arterial blood whenever SaO 2 departs from the assumed value of 100% (Aso et al 2019). Such respiration-induced changes are typical in humans.…”
Section: Discussionmentioning
confidence: 99%
“…It is further shown that by accounting for the temporal shifts in the BOLD CO2 response, improved CVR estimates can be obtained ( Yao et al, 2021 ). Furthermore, this CO 2 -related shift structure can be associated with the lag structure that naturally occurs in the rs-fMRI signal ( Tong and Frederick, 2014 ; Aso et al, 2019 ), and can be capitalized to extract additional vascular information without CO 2 challenges.…”
Section: The Role Of Cvr In Resting-state Fmrimentioning
confidence: 99%